Obstacles to the Winner of the Mortgage Rights Execution Auction to Receive the Auction Object in Real Time - Tristania, Cendikia Salwa Fadhillah; Dewi , Amelia Sri Kusuma; Suwardiyati , Rumi; Alam, Zairul; Putri, Dhita Widya (Faculty of Law, Universitas Brawijaya, 2025)
The author raises the issue of the obstacles faced by the winner of the auction for the execution of mortgage rights in obtaining the auction object, especially in the event that the auction object is empty because of the background of the problems experienced by the auction winner in receiving the auction object that has been purchased in real terms. This research uses empirical research methods with a sociological juridical approach, by analysing secondary data (such as existing rules) and primary data obtained through interviews and observations at the research location. The lack of clarity and firmness of the rules regarding the real delivery of auction objects, as well as inadequate infrastructure, limited public knowledge, debtor non-compliance with the law, and a culture of breaking the law among debtors, resulted in the implementation of the delivery of auction objects in an empty and uninhabited state not running smoothly. The absence of clear regulations regarding the seller's responsibility in the real delivery of goods and the reluctance of debtors to vacate the auction object are significant obstacles. To ensure the smooth implementation of the auction, it is necessary to improve the regulations regarding the delivery of immovable objects and increase public awareness through socialisation efforts.